The Informal Sector and Economic Policy in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Proceedings of an AFRISTAT seminar, Bamako, 10-14 March 1997. Volumes 1 and 3. AFRISTATPO Box 1600, Bamako, Mali.Fax: +223 22 11 40Email: afristat@malinet.ml